2011
DOI: 10.1089/brain.2011.0064
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural Brain Connectivity in Healthy Carriers of the Autism Risk Gene,CNTNAP2

Abstract: Recently, carriers of a common variant in the autism risk gene, CNTNAP2, were found to have altered functional brain connectivity using functional MRI. Here we scanned 328 young adults with high-field (4-Tesla) diffusion imaging, to test the hypothesis that carriers of this gene variant would have altered structural brain connectivity. All participants (209 females, 119 males, age: 23.4 +/−2.17 SD years) were scanned with 105-gradient high angular diffusion imaging (HARDI) at 4 Tesla. After performing a whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 59 publications
3
95
0
Order By: Relevance
“…Imaging genetics has also implicated SNPs that were previously associated with autism (rs7794745 and rs2710102), and SLI, dyslexia, and communication in normal cohorts (rs2710102). [29][30][31][32] Carrying a 'risk' allele at these loci seems to correlate with altered structural and functional imaging measures. It has been suggested that the effects on structural and functional brain networks seen in individuals carrying these risk variants may underlie their association with disorders such as autism, SLI and schizophrenia.…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…Imaging genetics has also implicated SNPs that were previously associated with autism (rs7794745 and rs2710102), and SLI, dyslexia, and communication in normal cohorts (rs2710102). [29][30][31][32] Carrying a 'risk' allele at these loci seems to correlate with altered structural and functional imaging measures. It has been suggested that the effects on structural and functional brain networks seen in individuals carrying these risk variants may underlie their association with disorders such as autism, SLI and schizophrenia.…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…Many analyses of brain connectivity have been conducted in this way (Dennis et al, 2012a, b;Dennis and Thompson, 2012;Jahanshad et al, 2011Jahanshad et al, , 2012Zalesky, 2009;Zhan et al, 2012). Connectivity matrices were compiled using a processing pipeline described previously (Braskie et al, 2012a, b;Dennis et al, 2012b;Jahanshad et al, 2011Jahanshad et al, , 2012Nir et al, 2012a, b).…”
Section: Subjects and Diffusion Imaging Of The Brainmentioning
confidence: 99%
“…Candidate gene analyses have even suggested that connectome properties may be associated with genetic risk factors for diseases and disorders such as autism (Scott-Van Zeeland et al 2010;Dennis et al 2011), schizophrenia (Braskie et al 2012), and dementia Jahanshad et al 2012); given the history of candidate gene associations in psychiatric genetics, these findings will need to be replicated Fig. 1 Various forms of connectivity measures extracted from brain images; all these methods allow us to study the brain from a higher dimensional perspective and observe correlations and connections between regions.…”
Section: Genetic Screening Of the Connectomementioning
confidence: 99%